Integrative Crop‐Soil‐Management Modeling to Assess Global Phosphorus Losses from Major Crop Cultivations. Issue 7 (20th July 2018) - Liu, Wenfeng; Yang, Hong; Ciais, Philippe; Stamm, Christian; Zhao, Xu; Williams, Jimmy R.; Abbaspour, Karim C.; Schulin, Rainer
Abstract: Fertilization, crop uptake followed by plant harvest, runoff and erosion, and transformations of phosphorus (P) in soil are the major factors influencing the P balance of croplands. It is important to integrate plant‐soil‐management interactions into consistent modeling systems to determine the effect of P fertilization conditions on yields and to quantify P losses. Previous assessment of P losses on large scales did not consider the interactions among these factors. Here we applied a grid‐based crop model to estimate global P losses from three most produced crops: maize, rice, and wheat. The model was forced by detailed P input data sets over the period 1998–2002. According to our simulations, global P losses from the three crops reached 1.2 Tg P/year, and about 44% of it was due to soil erosion. The global total P losses were dominated by contributions from a few hot spot regions. Reducing P fertilizer in regions experiencing excessive P uses and hence losses, especially in China and India, could achieve the same yields as today and save about two thirds of global total P inputs, with the cobenefits of declining global total P losses by 41% and downstream water quality improvement. Reducing soil erosion and retaining more crop residues on croplands could further save P inputs and alleviate P losses. This study is of significance to determine the major factors influencing P balance across regions of the world and help policy makers to propose efficient strategies for tackling P‐driven environmental problems. Key Points: We conduct an integrative crop‐soil‐management assessment of global phosphorus losses from major crop cultivations Phosphorus losses are concentrated on small hot spot regions, while crop yields do not show consistent patterns Optimizing phosphorus inputs in regions with excessive uses can significantly reduce phosphorus losses without compromising crop yields